Visual impairment and employment in Norway - Audun Brunes; Trond Heir (BMC, 2022)
Abstract Background Past studies have suggested lower employment of people with visual impairment. Reasons for this are less known. This study aimed to examine the employment rates among people with visual impairment, and its association with sociodemographic characteristics, vision-related factors, depression, and life satisfaction. Methods This cross-sectional study included a stratified random sample of 574 working-age adults (18-67 years) who were members of the Norwegian Association of the Blind and Partially Sighted. Data were collected by telephone interviews between January and May 2017, and included information on work status, sociodemographic factors, vision-related characteristics, depression (Patient Health Questionnaire-9), and life satisfaction (Cantril's Ladder of Life Satisfaction). Associations with employment (full-time, part-time, or self-employment) were examined using regression analyses. Results Of the participants, 51.2% of males and 38.1% of females reported to be employed. Employment was associated with being of middle age, male gender, higher education, residing in high-income municipalities, having a moderate degree of vision loss, lower onset-age of vision loss, and having no additional impairments. Employed participants had lower levels of depression compared to others (adjusted exponentiated beta: 0.80, 95% confidence interval (CI): 0.67, 0.96). They also had a higher odds of scoring higher on life satisfaction (adjusted exponentiated beta (odds ratio): 1.85, 95% CI: 1.32, 2.59). Conclusions Employment was lower in people with visual impairment than in the general population. Inclusion of the blind and partially sighted into the workforce could promote health and thus have socio-economic benefits.